Rohingya Refugees in Southeast Asia: Problems and Proposed Solutions in Historical Analysis - Oktafia, Sri Wahyuni; Pratama, Adiva Wildan (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2024)
Abstract: This study discusses the humanitarian crisis involving the Rohingya, one of the most persecuted minority groups in the world. They are forced to flee and drift at sea in hopes of finding a better life. The aim of this research is to highlight the issues associated with the Rohingya refugee crisis and propose potential solutions. By using a qualitative approach and utilizing the concepts of crisis and refugees, this study examines the Rohingya refugee crisis. The findings of the study indicate that the Rohingya ethnic group has been experiencing a humanitarian crisis since the 1970s, forcing them to flee. The issues arising from this refugee crisis include the Rohingya Muslim group being stranded, rejected, experiencing death, starvation, suffering, and human trafficking. The solutions presented in this study, which also represent a novelty in the research, include: (1) The international community, particularly the UN, should evaluate its support and mediate between Myanmar and the refugees. (2) ASEAN countries must be more proactive in addressing the crisis. (3) Reform policies to ensure inclusivity and justice for all ethnic groups. (4) Criticize Myanmar’s policies toward the Rohingya through interfaith dialogue. Abstrak: Studi ini membahas krisis kemanusiaan yang dialami oleh Rohingya, salah satu kelompok minoritas yang paling teraniaya di dunia. Mereka terpaksa melarikan diri dan terombang-ambing di laut dengan harapan menemukan kehidupan yang lebih baik. Penelitian ini bertujuan untuk menyoroti permasalahan yang terkait dengan krisis pengungsi Rohingya dan mengusulkan solusi potensial. Dengan menggunakan pendekatan kualitatif serta konsep krisis dan pengungsi, studi ini menganalisis krisis pengungsi Rohingya. Temuan dalam penelitian ini menunjukkan bahwa kelompok etnis Rohingya telah mengalami krisis kemanusiaan sejak tahun 1970-an yang memaksa mereka untuk melarikan diri. Permasalahan yang muncul dari krisis ini mencakup kelompok Muslim Rohingya yang terdampar, ditolak, mengalami kematian, kelaparan, penderitaan, hingga perdagangan manusia. Solusi yang diajukan dalam studi ini menekankan pentingnya evaluasi dukungan komunitas internasional, terutama PBB, serta peran aktif negara-negara ASEAN dalam menangani krisis tersebut. Selain itu, diperlukan reformasi kebijakan untuk memastikan inklusivitas dan keadilan bagi semua kelompok etnis di Myanmar serta penguatan dialog lintas agama untuk mengkritisi kebijakan diskriminatif yang diterapkan terhadap Rohingya.